Comparison of Nuclear Energy and Renewable Energy Consumption in terms of Energy Efficiency: An Analysis on The EU Members and Candidates - İskenderoğlu, Ömer; Akdağ, Saffet (International Journal of Energy Economics and Policy, 2019)
Energy efficiency is one of the main dynamics of sustainable development. As energy is used efficiently, the energy need for economic growth will be reduced, and the costs of energy sources will be reduced. In this context, nuclear and renewable energy are compared in terms of energy efficiency. The data of the energy efficiency index of 13 countries and the data on nuclear energy and renewable energy consumption over the years 1995-2016 and the DOLS and FMOLS tests are performed. As a result of the analysis, it is determined that there is a long-term relationship between the variables and that both energy sources have a positive effect on energy efficiency, but renewable energy is more advantageous than nuclear energy in terms of energy efficiency. Keywords: Nuclear Energy, Renewable Energy, Energy efficiency, Cointegration JEL Classifications: C33, O13, Q42, Q47 DOI: https://doi.org/10.32479/ijeep.7866